The unfinished corner - Colman, Dani (Wonderbound, 2021)
"Jewish mythology says that when G-d created the universe, a tiny corner of it was left unfinished. Opinion is divided on why, but everyone agrees that it's a dangerous place full of monsters. Twelve-year-old Miriam neither knows nor cares-- she's too busy preparing for her Bat Mitzvah, wrestling with whether she even wants to be Jewish-- until a peculiar angel appears, whisking her, her two best friends, and her worst frenemy off to this monstrous land with a single mission: finish the Unfinished Corner." -- Back cover